Teacher's Speech Acts in Indonesian Language Learning at Islamic Boarding School - Rinda Cahya Mudiawati; Khairun Nisyah; Widyatmike Gede Mulawarman (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
Pesantren, or Islamic boarding school, is one of the places where speech acts occur between teachers and students. The linguistic phenomena in the Islamic boarding school environment are very diverse. This study aimed to describe teachers' speech acts in learning the Indonesian language in class VIII at Islamic Boarding School Salsabila Samarinda, focusing on exploring locutionary, illocutionary, and perlocutionary acts. This study used a qualitative descriptive research method to describe the phenomenon. The data source was the teacher's speech in Indonesian language learning. The data collection techniques used in this research were observation, recording, and transcription. In this study, the data obtained were the results of recordings that were transcribed to obtain written notes from the subject. The data analysis techniques used were collecting, analyzing, and interpreting data. The results showed that the speech acts found in Indonesian language learning are locutionary acts in the form of news and question, illocutionary acts in the form of directive utterances, and perlocutionary acts of convivial and motivational functions. The locutionary acts spoken by the teacher in the Indonesian language learning process were 52 utterances, illocutionary acts were 30 utterances, perlocutionary acts were 25. The teacher’s speech acts in the boarding school environment have particular characteristics like using Islamic terms, Arabic language, and containing religious motivation in the utterances. The results of this research might have implications to contribute to insights about locutionary, illocutionary, and perlocutionary acts in the boarding school environment.